Thermoneutrality decreases thermogenic program and promotes adiposity in high‐fat diet‐fed mice. Issue 10 (26th May 2016) - Cui, Xin; Nguyen, Ngoc Ly T.; Zarebidaki, Eleen; Cao, Qiang; Li, Fenfen; Zha, Lin; Bartness, Timothy; Shi, Hang; Xue, Bingzhong
Abstract: Brown/beige adipocytes are therapeutic targets to combat obesity due to their abilities to dissipate energy through adaptive thermogenesis. Most studies investigating induction of brown/beige adipocytes were conducted in cold condition (e.g., 4°C); much is unknown about how the thermogenic program of brown/beige adipocytes is regulated in thermoneutral condition (e.g., 30°C), which is within the thermal comfort zone of human dwellings in daily life. Therefore, this study aims to characterize the thermogenic program of brown/beige adipocytes in mice housed under ambient (22°C) versus thermoneutral condition (30°C). Male mice raised at 22°C or 30°C were fed either chow diet or high‐fat (HF) diet for 20 weeks. Despite less food intake, chow‐fed mice housed at 30°C remained the same body weight compared to mice at 22°C. However, these thermoneutrally housed mice displayed a decrease in the expression of thermogenic program in both brown and white fat depots with larger adipocytes. When pair‐fed with chow diet, thermoneutrally housed mice showed an increase in body weight. Moreover, thermoneutrality increased body weight of mice fed with HF diet. This was associated with decreased expression of the thermogenic program in both brown and white fat depots of the thermoneutrally housed mice. The downregulation of the thermogenic program might have resulted from decreased sympathetic drive in the thermoneutrally housed mice evident by decreased expression of tyrosine hydroxylase expression and norepinephrine turnover in both brown and white fat depots. Our data demonstrate that thermoneutrality may negatively regulate the thermogenic program and sympathetic drive, leading to increased adiposity in mice. Abstract : Our study demonstrates that thermoneutrality may negatively regulate the thermogenic program and sympathetic drive, leading to increased adiposity in mice.